DIGITAL TECHNOLOGY LITERATION TO GROW ENTREPRENEURIAL SKILLS FOR HOUSEWIVES - Winarsih, Eni; Furinawati, Yunita (Universitas Islam Negeri Alauddin Makassar, 2018)
The technological advancesthat more rapidly must be balance with knowledge and skill that can bring benefits in life. The utilization of internet networks and smartphone proper to directed in positive things, one of them is with use it for work up the entrepreneurial skill with online business. This Program Kemitraan Masyarakat collaborate with Madiun Women Centre (MWC) which is organization that focus on activity for dealing with women’s problems and households in Madiun. The aims of technology literacy training and this literacy digital is to provide skills for housewives to take benefits by smartphones for entrepreneurial with online business. The online business is more interested insociety. The method used is by conducting business class which was attended by 30 people for 3 months which include training and mentoring online business. The material of business class includes: Step by step starting an online business, online business challenges, social media optimizing strategy in business promotion, choosing the angle of product photos to get commercial product results, utilization of photo applications to support product photos and promotions continued with practice and mentoring.The result of this activity covering: 16 participants have online business and willing to develop their business, and 14 participants who will be starting a business. Somme maximize online business through social media Instagram, Facebook, WhatsApp group and an increasing skill in making imaged products.